2014
DOI: 10.1534/genetics.114.167668
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation in Tunably Rugged Fitness Landscapes: The Rough Mount Fuji Model

Abstract: Much of the current theory of adaptation is based on Gillespie's mutational landscape model (MLM), which assumes that the fitness values of genotypes linked by single mutational steps are independent random variables. On the other hand, a growing body of empirical evidence shows that real fitness landscapes, while possessing a considerable amount of ruggedness, are smoother than predicted by the MLM. In the present article we propose and analyze a simple fitness landscape model with tunable ruggedness based on… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(115 citation statements)
references
References 83 publications
7
108
0
Order By: Relevance
“…Moreover, because multiple alleles at the same site are contained within the landscape, we may study whether changes in the shape of the landscape are site-or amino acid-specific. We computed various landscape statistics (roughness-to-slope ratio, fraction of epistasis, and the recently proposed gamma statistics; SI Appendix, Supporting Information 1: Extended Materials and Methods) (10,11,14) and compared them with expectations from theoretical landscape models [NK (36)(37)(38), RMF (39,40), HoC (41), egg-box landscapes (14); for brief definitions of these terms, see SI Appendix, Supporting Information 2: Overview of Different Fitness Landscape Models Introduced in the Main Text]. Whenever necessary, we provide an analytical extension of the used statistic to the case of multiallelic landscapes (Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, because multiple alleles at the same site are contained within the landscape, we may study whether changes in the shape of the landscape are site-or amino acid-specific. We computed various landscape statistics (roughness-to-slope ratio, fraction of epistasis, and the recently proposed gamma statistics; SI Appendix, Supporting Information 1: Extended Materials and Methods) (10,11,14) and compared them with expectations from theoretical landscape models [NK (36)(37)(38), RMF (39,40), HoC (41), egg-box landscapes (14); for brief definitions of these terms, see SI Appendix, Supporting Information 2: Overview of Different Fitness Landscape Models Introduced in the Main Text]. Whenever necessary, we provide an analytical extension of the used statistic to the case of multiallelic landscapes (Materials and Methods).…”
Section: Resultsmentioning
confidence: 99%
“…However, since our analysis neglects the effect of fluctuations, the subleading behavior of (60) cannot generally be expected to be exact. The leading order behavior D RAW ≈ (ln L) 1/γ /A with A and γ given in (21) and (22), respectively, is compared to simulations in figure 8, showing excellent agreement.…”
Section: By the Change Of Variablesmentioning
confidence: 59%
“…To sum up, we found that where γ and A are given in (22) and (21). Hence, the MFA becomes exact as l → ∞.…”
Section: Discussionmentioning
confidence: 79%
“…In most cases the computational and experimental cost of analyzing empirical models has required simplified sequence spaces, especially binary sequences (indicating only the presence or absence of a mutation at each site) [3,5,8,9], genomes or proteins with reduced lengths [14][15][16], and reduced alphabets of amino acids [16,17] or protein structural components [18]. However, it is not clear how properties of landscapes and evolutionary paths change under these implicit coarse-graining schemes.…”
Section: Introductionmentioning
confidence: 99%